Evaluation of IS200-PCR and Comparison with Other Molecular Markers To Trace Salmonella enterica subsp. enterica Serotype Typhimurium Bovine Isolates from Farm to Meat - Millemann, Yves (American Society for Microbiology, 2000)
A procedure that uses an original molecular marker (IS200-PCR) and that is based on the amplification of DNA with outward-facing primers complementary to each end of IS200 has been evaluated with a collection of 85 Salmonella enterica subsp. enterica serotype Typhimurium isolates. These strains were isolated from a group of 10 cows at different stages: during transportation between the farm and the slaughterhouse, on the slaughter line, from the environment, and from the final product (ground beef). The 85 isolates were characterized by their antibiotic resistance patterns and were compared by IS200-PCR and by use of four other genotypic markers. Those markers included restriction profiles for 16S and 23S rRNA (ribotypes) and amplification profiles obtained by different approaches: random amplified polymorphic DNA analysis, enterobacterial repetitive intergenic consensus PCR, and PCR ribotyping. The results of the IS200-PCR were in accordance with those of other molecular typing methods for this collection of isolates. Five different genotypes were found, which made it possible to refine the hypotheses on transmission obtained from phenotypic results. The genotyping results indicated the massive contamination of the whole group of animals and of the environment by one clonal strain originally recovered from one cow that excreted the strain. On the other hand, a few animals and their environment appeared to be simultaneously contaminated with genetically different strains.